2013
DOI: 10.1128/aem.01037-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a NaCl-Responsive Genetic Locus Involved in Survival during Desiccation in Sinorhizobium meliloti

Abstract: The Rhizobiaceae are a bacterial family of enormous agricultural importance due to the ability of its members to fix atmospheric nitrogen in an intimate relationship with plants. Their survival as naturally occurring soil bacteria in agricultural soils as well as popular seed inocula is affected directly by drought and salinity. Survival after desiccation in the presence of NaCl is enabled by underlying genetic mechanisms in the model organism Sinorhizobium meliloti 1021. Since salt stress parallels a loss in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…viciae 3841, namely RL2376, was found to bind d -galactose and its use as a biosensor was proposed [ 55 ], although it is highly likely to also bind l -arabinose and might not be particularly selective. Another study found that the GafA Sm -encoding operon was expresed in response to desiccation induced by high NaCl in Sinorhizobium meliloti 1021 [ 56 ], and a known response to this is the production of galactose-containing oligosaccharides [ 57 ], consistent with a function of scavenging d -galactose to provide precursors for these glycans.…”
Section: Discussionmentioning
confidence: 99%
“…viciae 3841, namely RL2376, was found to bind d -galactose and its use as a biosensor was proposed [ 55 ], although it is highly likely to also bind l -arabinose and might not be particularly selective. Another study found that the GafA Sm -encoding operon was expresed in response to desiccation induced by high NaCl in Sinorhizobium meliloti 1021 [ 56 ], and a known response to this is the production of galactose-containing oligosaccharides [ 57 ], consistent with a function of scavenging d -galactose to provide precursors for these glycans.…”
Section: Discussionmentioning
confidence: 99%
“…However, how likely is to have a molecular junction of a NaCl inducible gene that, when knocked out, leads to temperature dependent desiccation sensitivity? In addition to some NaCl induced loci described earlier, locus smb01590, found by Vriezen et al [2013], also affects survival during desiccation (Figure 4). Interestingly, the ability of the mutant carrying a Tn5luxAB insertion in ORF smc01590 (Sce-1) to survive desiccation is better, albeit not significant (P=0.22), than that of the reference strain at In mutant Sce-1, it appears that the inability to correctly adjust the membrane midpoint temperature at increased temperature leads to the opposite effect.…”
Section: Effect Of Osmotic and Salt Stressmentioning
confidence: 67%
“…These cellular lifestyles occur in very different environments and the soil environment particularly can involve widely varying physicochemical conditions. Accordingly, S. meliloti has been the subject of attempts to identify genes that when disrupted conditionally impair growth under stressful conditions that include high salinity (Wei et al, 2004;Domínguez-Ferreras et al, 2006;Miller-Williams et al, 2006;Vriezen et al, 2013;Calatrava-Morales et al, 2017), low pH (Reeve et al, 1998;Lagares et al, 2016;Albicoro et al, 2021), oxidative stress (Davies and Walker, 2007;Flechard et al, 2009;Lehman and Long, 2018) and other physical or chemical conditions.…”
Section: Introductionmentioning
confidence: 99%